Copper-chromium-beryllium-zirconium alloy bar and preparation method thereof
By adding beryllium elements to the copper-chromium zirconium alloy and aging treatment, the problem of low hardness of existing copper-chromium zirconium alloys has been solved, and the hardness is significantly improved and the conductive performance is optimized, which is suitable for the production of welding conductive nozzles.
Patent Information
- Application Number
- CN202411973660.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing copper-chromium-zirconium alloy has low hardness and is difficult to meet the demand for high hardness and conductivity in welding production.
By adding beryllium elements during the smelting of copper-chromium zirconium alloy and performing aging treatment, high-temperature phases such as Cr phase, CuBe phase, CuZr phase and CrBe2 are precipitated to improve the high-temperature strength of the alloy.
It significantly improves the hardness of copper-chromium beryllium zirconium alloy, maintains excellent mechanical properties and electrical conductivity, and extends service life.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nonferrous metal preparation, and in particular to a copper-chromium-beryllium-zirconium alloy rod and a preparation method thereof. Background Art
[0002] Copper-chromium-zirconium alloy has comprehensive properties such as high strength, high hardness and wear resistance. It is a key material for making conductive nozzles, resistance welding electrodes, etc., and has been widely used in the field of welding. With the development of science and technology, the performance requirements of copper alloys in the field of welding are getting higher and higher. It is urgent to further improve the hardness of copper-chromium-zirconium alloy without reducing the conductivity too much, so as to extend the service life of copper-chromium-zirconium alloy. Therefore, the development of high-hardness and high-conductivity copper-chromium-zirconium alloy is of great significance to meet the needs of welding production.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a copper-chromium-beryllium-zirconium alloy rod and a preparation method thereof, so as to overcome the problem of low hardness of the existing copper-chromium-zirconium alloy.
[0005] The present invention is achieved in that:
[0006] In a first aspect, the present invention provides a method for preparing a copper-chromium-beryllium-zirconium alloy rod, comprising the following steps:
[0007] Smelting, melting raw materials including copper, chromium, beryllium and zirconium to obtain a melt;
[0008] Continuous casting: forming copper-chromium-beryllium-zirconium alloy ingots in an inert gas atmosphere;
[0009] Drawing, drawing the copper-chromium-beryllium-zirconium alloy ingot to form a rod;
[0010] Aging treatment: subjecting the rod to aging treatment in an inert gas atmosphere and cooling it with the furnace to obtain the copper-chromium-beryllium-zirconium alloy rod, wherein the aging treatment temperature is 400° C. to 500° C. and the time is 2 h to 6 h.
[0011] In an optional embodiment, the raw material includes, by mass fraction, 0.3% to 1.0% chromium, 0.2% to 0.8% beryllium, 0.1% to 0.3% zirconium, and the remainder copper and unavoidable impurities.
[0012] In an optional embodiment, the raw materials include cathode copper, copper-chromium master alloy, copper-beryllium master alloy and copper-zirconium master alloy.
[0013] In an optional embodiment, the chromium content in the copper-chromium master alloy is 10% to 15%;
[0014] And / or, the zirconium content in the copper-zirconium master alloy is 40% to 50%;
[0015] And / or, the beryllium content in the copper-beryllium master alloy is 2% to 4%.
[0016] In an optional embodiment, in the smelting step, the smelting temperature is 1350°C to 1500°C, and the vacuum degree is 0.1Pa to 10Pa.
[0017] In an optional embodiment, in the continuous casting step, the continuous casting speed is 1.5 cm / min-10 cm / min, the water inlet temperature is 20° C.-30° C., and the water flow rate is 1 LPM-5 LPM.
[0018] In an alternative embodiment, the drawing step temperature is 12°C-35°C.
[0019] In a second aspect, the present invention provides a copper-chromium-beryllium-zirconium alloy rod, which is prepared by the method described in the aforementioned embodiment.
[0020] In an optional embodiment, the copper-chromium-beryllium-zirconium alloy rod comprises Cr phase, CuBe phase, CuZr phase and CrBe phase. 2 Mutually.
[0021] In an optional embodiment, the copper-chromium-beryllium-zirconium alloy rod has a hardness greater than 88 HRB and a conductivity greater than 77% IACS;
[0022] And / or, the diameter of the copper-chromium-beryllium-zirconium alloy rod is 6 mm-10 mm.
[0023] The present invention has the following beneficial effects:
[0024] The present invention adds beryllium element during the smelting process of copper-chromium-zirconium alloy and performs aging treatment at the same time. In the aging process, not only Cr phase, CuBe phase and CuZr phase are precipitated, but also CrBe phase is precipitated. 2 High temperature phases such as quartz and pyrolysis are beneficial to further improve the high temperature strength of the alloy, thereby increasing the service life of the alloy.
[0025] The copper-chromium-beryllium-zirconium alloy prepared by the present application has significantly improved hardness and has excellent mechanical properties and electrical conductivity, and has broad application prospects for making welding conductive nozzles. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0027] The embodiment of the present invention provides a method for preparing a copper-chromium-beryllium-zirconium alloy rod, comprising the following steps:
[0028] Smelting, melting raw materials including copper, chromium, beryllium and zirconium to obtain a melt;
[0029] Continuous casting: forming copper-chromium-beryllium-zirconium alloy ingots in an inert gas atmosphere;
[0030] Drawing, drawing the copper-chromium-beryllium-zirconium alloy ingot to form a rod;
[0031] Aging treatment: subjecting the rod to aging treatment in an inert gas atmosphere and cooling it with the furnace to obtain the copper-chromium-beryllium-zirconium alloy rod, wherein the aging treatment temperature is 400° C. to 500° C. and the time is 2 h to 6 h.
[0032] The present invention adds beryllium element during the smelting process of copper-chromium-zirconium alloy and performs aging treatment at the same time. In the aging process, not only Cr phase, CuBe phase and CuZr phase are precipitated, but also CrBe phase is precipitated. 2 High temperature phases such as quartz and pyrolysis are beneficial to further improve the high temperature strength of the alloy, thereby increasing the service life of the alloy.
[0033] In the present application, the continuous casting method is adopted to prepare the ingot, which can not only improve the production efficiency, but also help to improve the performance of the copper-chromium-beryllium-zirconium alloy. The hardness of the prepared copper-chromium-beryllium-zirconium alloy is significantly improved, and it has excellent mechanical properties and electrical conductivity. It has broad application prospects for the production of welding conductive nozzles.
[0034] In the present application, the temperature of the aging treatment is 400°C to 500°C, specifically 400°C, 420°C, 440°C, 460°C, 480°C, 500°C or any value between 400°C and 500°C; the time is 2h to 6h, specifically 2h, 3h, 4h, 5h, 6h or any value between 2h and 6h. If the aging treatment temperature is too high, not only will the conductivity of the alloy be significantly reduced, but the hardness of the alloy will also drop.
[0035] In an optional embodiment, the raw material includes, by mass fraction, 0.3% to 1.0% chromium, 0.2% to 0.8% beryllium, 0.1% to 0.3% zirconium, and the remainder copper and unavoidable impurities.
[0036] The amount of each component has an important influence on the performance of copper-chromium-beryllium-zirconium alloy. In particular, too low content of beryllium and chromium is not conducive to the performance of CrBe 2 However, if the beryllium and chromium content is too high, it will lead to a decrease in hardness.
[0037] In an optional embodiment, the raw materials include cathode copper, copper-chromium master alloy, copper-beryllium master alloy and copper-zirconium master alloy.
[0038] In an optional embodiment, the chromium content in the copper-chromium master alloy is 10% to 15%;
[0039] And / or, the zirconium content in the copper-zirconium master alloy is 40% to 50%;
[0040] And / or, the beryllium content in the copper-beryllium master alloy is 2% to 4%.
[0041] Using master alloy as raw material is beneficial to improving the uniformity of the melt, reducing segregation, reducing the introduction of non-metallic inclusions, and is conducive to obtaining better organizational structure and performance consistency.
[0042] In an optional embodiment, in the smelting step, the smelting temperature is 1350°C to 1500°C, and the vacuum degree is 0.1Pa to 10Pa.
[0043] Melting under this condition helps to ensure that all components are completely dissolved and fully mixed, while removing some gases and inclusions, which is crucial to improving the conductivity of the alloy.
[0044] In an optional embodiment, in the continuous casting step, the continuous casting speed is 1.5 cm / min-10 cm / min, the water inlet temperature is 20° C.-30° C., and the water flow rate is 1 LPM-5 LPM.
[0045] In the continuous casting step, the continuous casting speed affects the surface quality of the ingot and is within the range of 1.5 cm / min-10 cm / min, specifically 1.5 cm / min, 2 cm / min, 4 cm / min, 6 cm / min, 8 cm / min, 10 cm / min or any value between 1.5 cm / min and 10 cm / min, which can take into account both the ingot quality and production efficiency. If the continuous casting speed is too fast, it will lead to an increase in surface defects of the ingot and reduce the conductivity. The water inlet temperature can be 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, and the water flow rate can be 1LPM, 2LPM, 3LPM, 4LPM, 5LPM. The water inlet temperature and water flow rate will affect the cooling rate, and then affect the grain size and the type, quantity, size and distribution of the precipitated phase. In the present application, rapid cooling is conducive to the formation of a fine and uniform grain structure, which is conducive to improving the hardness and conductivity.
[0046] In an alternative embodiment, the drawing step temperature is 12°C-35°C.
[0047] An embodiment of the present invention further provides a copper-chromium-beryllium-zirconium alloy rod, which is prepared by the method described in the above embodiment.
[0048] In an optional embodiment, the copper-chromium-beryllium-zirconium alloy rod comprises Cr phase, CuBe phase, CuZr phase and CrBe phase. 2 Mutually.
[0049] In an optional embodiment, the copper-chromium-beryllium-zirconium alloy rod has a hardness greater than 88 HRB and a conductivity greater than 77% IACS;
[0050] And / or, the diameter of the copper-chromium-beryllium-zirconium alloy rod is 6 mm-10 mm.
[0051] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0052] Example 1
[0053] This embodiment provides a method for preparing a copper-chromium-beryllium-zirconium alloy rod with a diameter of 6 mm, which specifically includes the following steps:
[0054] Cathode copper, copper-chromium, copper-beryllium and copper-zirconium master alloy are used as raw materials, wherein the raw materials include 1.0% chromium, 0.7% beryllium, 0.3% zirconium and the rest of copper and inevitable impurities, and are melted at a vacuum degree of 0.1 Pa and 1350°C; a copper-chromium-beryllium-zirconium alloy billet is directionally solidified and continuously cast in an argon atmosphere, with a continuous casting speed of 10 cm / min, a water inlet temperature of 20°C and a water flow rate of 1 LPM; the copper-chromium-beryllium-zirconium alloy billet is drawn at room temperature to a diameter of 6 mm; the copper-chromium-beryllium-zirconium alloy rod after room temperature drawing is subjected to aging treatment in an argon atmosphere, with an aging treatment temperature of 400°C, a time of 6 hours, and a cooling method of furnace cooling. The prepared copper-chromium-beryllium-zirconium alloy rod has a hardness of 91HRB and a conductivity of 77%IACS.
[0055] Example 2
[0056] This embodiment provides a method for preparing a copper-chromium-beryllium-zirconium alloy rod with a diameter of 8 mm, which specifically includes the following steps:
[0057] Cathode copper, copper-chromium, copper-beryllium and copper-zirconium master alloy are used as raw materials, wherein the raw materials include 0.8% chromium, 0.2% beryllium, 0.3% zirconium and the rest copper and inevitable impurities, and are melted at a vacuum degree of 10Pa and 1450°C; a copper-chromium-beryllium-zirconium alloy billet is directionally solidified and continuously cast in an argon atmosphere, with a continuous casting speed of 5cm / min, a water inlet temperature of 25°C and a water flow rate of 3LPM; the copper-chromium-beryllium-zirconium alloy billet is drawn at room temperature to a diameter of 8mm; the copper-chromium-beryllium-zirconium alloy rod after room temperature drawing is aged in an argon atmosphere, with an aging treatment temperature of 450°C, a time of 4h, and a cooling method of furnace cooling. The prepared copper-chromium-beryllium-zirconium alloy rod has a hardness of 90.5HRB and a conductivity of 78%IACS.
[0058] Example 3
[0059] This embodiment provides a method for preparing a copper-chromium-beryllium-zirconium alloy rod with a diameter of 8.8 mm, which specifically includes the following steps:
[0060] Cathode copper, copper-chromium, copper-beryllium and copper-zirconium master alloy are used as raw materials, wherein the raw materials include 0.5% chromium, 0.5% beryllium, 0.15% zirconium and the rest of copper and inevitable impurities, and are melted at a vacuum degree of 5Pa and 1480°C; a copper-chromium-beryllium-zirconium alloy billet is directionally solidified and continuously cast in an argon atmosphere, with a continuous casting speed of 8cm / min, a water inlet temperature of 28°C and a water flow rate of 4LPM; the copper-chromium-beryllium-zirconium alloy billet is drawn at room temperature to a diameter of 8.8mm; the copper-chromium-beryllium-zirconium alloy rod after room temperature drawing is aged in an argon atmosphere, with an aging treatment temperature of 460°C, a time of 3h, and a cooling method of furnace cooling. The prepared copper-chromium-beryllium-zirconium alloy rod has a hardness of 89HRB and a conductivity of 78.5%IACS.
[0061] Example 4
[0062] This embodiment provides a method for preparing a copper-chromium-beryllium-zirconium alloy rod with a diameter of 10 mm, which specifically includes the following steps:
[0063] Cathode copper, copper-chromium, copper-beryllium and copper-zirconium master alloy are used as raw materials, wherein the raw materials include 0.3% chromium, 0.8% beryllium, 0.2% zirconium and the rest of copper and inevitable impurities, and are melted at a vacuum degree of 10Pa and 1500°C; a copper-chromium-beryllium-zirconium alloy billet is directionally solidified and continuously cast in an argon atmosphere, with a continuous casting speed of 1.5cm / min, a water inlet temperature of 28°C and a water flow rate of 5LPM; the copper-chromium-beryllium-zirconium alloy billet is drawn at room temperature to a diameter of 10mm; the copper-chromium-beryllium-zirconium alloy rod after room temperature drawing is aged in an argon atmosphere, with an aging treatment temperature of 500°C, a time of 2h, and a cooling method of furnace cooling. The prepared copper-chromium-beryllium-zirconium alloy rod has a hardness of 88.5HRB and a conductivity of 79%IACS.
[0064] Comparative Example 1
[0065] The only difference between this comparative example and Example 1 is that no beryllium is added to the raw materials, and the mass ratio of copper, chromium and zirconium remains unchanged.
[0066] Comparative Example 2
[0067] The only difference between this comparative example and Example 1 is that no aging treatment is performed after drawing.
[0068] Comparative Example 3
[0069] The only difference between this comparative example and comparative example 1 is that no aging treatment is performed after drawing.
[0070] Comparative Example 4
[0071] The only difference between this comparative example and Example 1 is that the aging treatment temperature is 350° C. and the time is 8 h.
[0072] Comparative Example 5
[0073] The only difference between this comparative example and Example 1 is that the aging treatment temperature is 550° C. and the time is 1 h.
[0074] Comparative Example 6
[0075] The only difference between this comparative example and Example 1 is that beryllium is replaced with an equal mass of niobium.
[0076] Comparative Example 7
[0077] The only difference between this comparative example and Example 1 is that beryllium is replaced by an equal mass of magnesium.
[0078] Comparative Example 8
[0079] The only difference between this comparative example and Example 1 is that non-vacuum melting casting is used to replace the continuous casting step. The specific steps of the process are: first, smelting at 1300°C in an atmospheric environment and then casting into an ingot; then hot forging into a rod at 940°C; then quenching at 960°C and drawing to an outer diameter of 6 mm; finally, aging treatment temperature is 400°C, time is 6 hours, and cooling method is furnace cooling.
[0080] Comparative Example 9
[0081] The only difference between this comparative example and Example 1 is that the continuous casting speed is too fast, which easily causes leakage and crack defects. Specifically, the continuous casting speed is 15 cm / min, the water inlet temperature is 20° C., and the water flow rate is 1 LPM.
[0082] Comparative Example 10
[0083] The only difference between this comparative example and Example 1 is that the continuous casting speed is too slow, the solid-liquid interface penetrates deeper into the crystallizer, and the ingot is easily rubbed against the crystallizer wall, resulting in crack defects. Specifically, the continuous casting speed is 0.5 cm / min, the water inlet temperature is 20°C, and the water flow rate is 1 LPM.
[0084] The hardness and conductivity of the copper-chromium-beryllium-zirconium alloy rod prepared in the above embodiment were tested, and the results are shown in Table 1.
[0085] Table 1 Hardness and conductivity of materials
[0086] Hardness HRB Electrical conductivity %IACS Example 1 91 77 Example 2 90.5 78 Example 3 89 78.5 Example 4 88.5 79 Comparative Example 1 80 80 Comparative Example 2 72 48 Comparative Example 3 65 46 Comparative Example 4 78 77 Comparative Example 5 74 78 Comparative Example 6 80 78 Comparative Example 7 78 76 Comparative Example 8 83 65 Comparative Example 9 75.8 63 Comparative Example 10 81 75
[0087] Comparative Example 1 prepares a copper-chromium-beryllium-zirconium alloy rod with a hardness of 80HRB and a conductivity of 80%IACS. The hardness of the alloy prepared by the method of Example 1 is increased by more than 10%, while the conductivity is not reduced too much, which is beneficial to improving the life of the copper-chromium-beryllium-zirconium alloy conductive nozzle and has obvious performance advantages; at the same time, by comparing Example 1 with Comparative Examples 1-3 and 6-7, it can be seen that the aging treatment combined with the introduction of beryllium is more conducive to taking into account the hardness and conductivity of the alloy. If niobium is replaced with other metals, even after aging treatment, it is difficult to take into account the hardness and conductivity; by comparing Example 1 with Comparative Examples 4-5, it can be seen that the temperature of the aging treatment also has a more critical influence on the copper-chromium-beryllium-zirconium alloy rod; by comparing Example 1 with Comparative Example 8, it can be seen that the continuous casting method is more conducive to improving the performance of the alloy.
[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a copper-chromium-beryllium-zirconium alloy rod, characterized in that: The following steps are involved: Smelting, melting raw materials including copper, chromium, beryllium and zirconium to obtain a melt; Continuous casting: forming copper-chromium-beryllium-zirconium alloy ingots in an inert gas atmosphere; Drawing, drawing the copper-chromium-beryllium-zirconium alloy ingot to form a rod; Aging treatment: subjecting the rod to aging treatment in an inert gas atmosphere and cooling it with the furnace to obtain the copper-chromium-beryllium-zirconium alloy rod, wherein the aging treatment temperature is 400° C. to 500° C. and the time is 2 h to 6 h.
2. The method for preparing the copper-chromium-beryllium-zirconium alloy rod according to claim 1, characterized in that: Calculated by mass fraction, the raw material includes 0.3% to 1.0% chromium, 0.2% to 0.8% beryllium, 0.1% to 0.3% zirconium and the remainder of copper and inevitable impurities.
3. The method for preparing the copper-chromium-beryllium-zirconium alloy rod according to claim 1, characterized in that: The raw materials include cathode copper, copper-chromium master alloy, copper-beryllium master alloy and copper-zirconium master alloy.
4. The method for preparing the copper-chromium-beryllium-zirconium alloy rod according to claim 3, characterized in that: The chromium content in the copper-chromium master alloy is 10% to 15%; And / or, the zirconium content in the copper-zirconium master alloy is 40% to 50%; And / or, the beryllium content in the copper-beryllium master alloy is 2% to 4%.
5. The method for preparing the copper-chromium-beryllium-zirconium alloy rod according to claim 1, characterized in that: In the smelting step, the smelting temperature is 1350°C to 1500°C, and the vacuum degree is 0.1Pa to 10Pa.
6. The method for preparing the copper-chromium-beryllium-zirconium alloy rod according to claim 1, characterized in that: In the continuous casting step, the continuous casting speed is 1.5 cm / min-10 cm / min, the water inlet temperature is 20°C-30°C, and the water flow rate is 1 LPM-5 LPM.
7. The method for preparing the copper-chromium-beryllium-zirconium alloy rod according to claim 1, characterized in that: The temperature of the drawing step is 12°C-35°C.
8. A copper-chromium-beryllium-zirconium alloy bar, characterized in that: Prepared by the method according to any one of claims 1 to 7.
9. The copper-chromium-beryllium-zirconium alloy rod according to claim 8, characterized in that: The copper-chromium-beryllium-zirconium alloy rod comprises a Cr phase, a CuBe phase, a CuZr phase and a CrBe2 phase.
10. The copper-chromium-beryllium-zirconium alloy rod according to claim 8, characterized in that: The copper-chromium-beryllium-zirconium alloy rod has a hardness greater than 88 HRB and a conductivity greater than 77% IACS; And / or, the diameter of the copper-chromium-beryllium-zirconium alloy rod is 6 mm-10 mm.
Citation Information
Patent Citations
Preparation method of high-softening-resistance copper-chromium-zirconium alloy bar
CN113736970A
Preparation method of high-strength and high-conductivity copper-chromium-zirconium alloy
CN115074564A
Electrode material for resistant welding and its manufacture
JP1995090429A
Copper alloy
JP2004100041A